Modelling the effects of railway implemented low-height noise screens; an investigation of train track ballast impedance - Hildén, Marius (My University, 2024)
Conventional tall noise barriers (measuring approximately 3 meters and above) are commonly employed to mitigate noise from railways in urban environments. They are effective and their noise reduction outcomes can be accurately estimated using existing, low-order geometrical ray-acoustic models, e.g. Pierce’s thin hard diffracting screen solution. However, tall noise barriers arguably have an adverse effect on surrounding landscape, as well as obscuring the sightlines of both train operators and passengers. In cases where noise levels can be adequately attenuated using a low-height noise screen (LHNS) it can be a preferable implementation in regard to aesthetic, cost, and maintenance aspects. The current problem with implementing LHNS is that their noise reduction outcomes are, due to fundamental design, difficult to accurately estimate. This is a problem in large-scale urban development projects where the margin of error is small, often leading to LHNS being disregarded in favor of conventional noise screens. To improve the accuracy of insertion loss (IL) estimations from LHNS, a previously imple mented 2.5D boundary element method (BEM) model used for calculating railway LHNS IL is revised. The main focus of the revision regards the surface impedance of the BEM-modeled train track. Measurements have been performed on ballasted train tracks to serve as validation data for an impedance parameter study of ballasted train track surfaces. The resulting set of impedance parameters have been used in 2.5D BEM-models simulating the sound pressure field of different train shapes with and without LHNS, in other words estimating the IL of LHNS for different railway applications. The IL results are compared with existing LHNS IL measurements from other projects. The simulated results demonstrate a generally accurate alignment with existing measurement data for IL in third-octave frequency bands for passenger trains, however results differ between different measurement comparisons. In the case of industrial trains, results are less promising. This is hypothesized to be a result of the source model used in the simulations being inaccurate for industrial trains. Further investigation/development of source models used for different train types is a recom mended starting point for improving the reliability of the 2.5D BEM simulations. Access to more LHNS IL measurement validation data is also considered necessary. Nonetheless, the yielded results indicate that the revised impedance parameters have been an effective step in improving LHNS IL estimation when compared with previous BEM-model results.
Keywords: low-height noise screen, low-height noise barrier, ballast impedance, acoustics, insertion loss, BEM